Fabrication of graphene oxide polymer composite particles with grafted poly(amidoamine) dendrimers and their application in ion chromatography. (24th April 2018) - Guo, Dandan; Lou, Chaoyan; Huang, Zhongping; Muhammad, Nadeem; Qiming, Zhao; Wu, Shuchao; Zhu, Yan
Abstract : Graphene oxide polymer composite particles with grafted PAMAM dendrimers and their application in ion chromatography. Abstract : In this work, a novel anionic adsorbent based on graphene oxide-coated polymer composite particles was synthesized by grafting with poly(amidoamine) dendrimers (PAMAM). The composite polymer particles (PS@GO) were prepared by coating an appropriate amount of graphene oxide (GO) sheets onto poly(styrene-divinyl benzene-glycidylmethacrylate) (PS-GMA) beads. PAMAM dendrimers were synthesized by the polymerization of ethylenediamine and methyl acrylate, and then grafted to the surface of PS@GO particles. Finally, the adsorbent was treated with 1, 4-butanediol diglycidyl ether (BDDGE) and characterized using various techniques. In the application, the adsorption capability of the synthesized adsorbent was investigated using the breakthrough curve method. According to the results, the adsorption capabilities were concluded to increase with increasing GO load and increasing PAMAM generation. Furthermore, this novel synthesized adsorbent was successfully used as a stationary phase for simultaneous isocratic separation of inorganic and organic anions in ion chromatography.